Characterization and potential roles of bone marrow-derived stromal cells in cancer development and metastasis - Kawai, Hotaka; Tsujigiwa, Hidetsugu; Siar, Chong Huat; Nakano, Keisuke; Takabatake, Kiyofumi; Fujii, Masae; Hamada, Mei; Tamamura, Ryo; Nagatsuka, Hitoshi (Ivyspring International Publisher, 2018)
Background: The tumor microenvironment and its stromal cells play an important role in cancer development and metastasis. Bone marrow-derived cells (BMDCs), a rich source of hematopoietic and mesenchymal stem cells, putatively contribute to this tumoral stroma. However their characteristics and roles within the tumor microenvironment are unclear. In the present study, BMDCs in the tumor microenvironment were traced using the green fluorescent protein (GFP) bone marrow transplantation model. Methods: C57BL/6 mice were irradiated and rescued by bone marrow transplantation from GFP-transgenic mice. Lewis lung cancer cells were inoculated into the mice to generate subcutaneous allograft tumors or lung metastases. Confocal microscopy, immunohistochemistry for GFP, α-SMA, CD11b, CD31, CD34 and CD105, and double-fluorescent immunohistochemistry for GFP-CD11b, GFP-CD105 and GFP-CD31 were performed. Results: Round and dendritic-shaped GFP-positive mononuclear cells constituted a significant stromal subpopulation in primary tumor peripheral area (PA) and metastatic tumor area (MA) microenvironment, thus implicating an invasive and metastatic role for these cells. CD11b co-expression in GFP-positive cells suggests that round/dendritic cell subpopulations are possibly BM-derived macrophages. Identification of GFP-positive mononuclear infiltrates co-expressing CD31 suggests that these cells might be BM-derived angioblasts, whereas their non-reactivity for CD34, CD105 and α-SMA implies an altered vascular phenotype distinct from endothelial cells. Significant upregulation of GFP-positive, CD31-positive and GFP/CD31 double-positive cell densities positively correlated with PA and MA (P<0.05). Conclusion: Taken together, in vivo evidence of traceable GFP-positive BMDCs in primary and metastatic tumor microenvironment suggests that recruited BMDCs might partake in cancer invasion and metastasis, possess multilineage potency and promote angiogenesis.